THERMAL BEHAVIOR OF SCAPOLITE ME79.6 AND ME33.3 - Antao S.M.; Hassan I. (My University, 2002)
Scapolite-group minerals have the general formula and TG) were carried out on two samples (Me79.6 and Me33.3) using a Netzsch STA 409 EP/3/D simultaneous TG-DTA apparatus and a Netzsch STA 449C simultaneous TG-DSC instrument. The DTA-TG results indicate that Me79.6 Ioses 5.7 wt.% in two steps at different rates: at 1171°C, CO2(g) and minor NaCl are lost together, followed by a small amount of SO3(g) at about 1232°C, and the residue melts at 1407°C. High-temperature X-ray-diffraction (XRD) data also indicate that the Me79.6 residue melts between 1300 and 1400°C. Me33.3 loses 5.2 wt.% of NaCl, CO2(g), and minor SO3(g) in a single step at 1199°C, and the residue melts at 1319°C. The residue of Me79.6 melts at a higher temperature than Me33.3 because its framework composition is closer to that of anorthite, whereas that of Me33.3 is closer to that of albite. The cage clusters [Na4•Cl]3+ and [NaCa3*CO3]5+ in Me33.3 are ordered, whereas the clusters [NaCa3*CO3]5+ and [Ca4*CO3]6+ in Me79.6 are disordered. The DSC curve for scapolite Me33.3 shows a transition at about 299°C arising from disordering of [Na4*Cl]3+ and [NaCa3*CO3]5+ clusters on heating.